How Naive Is Contentful Moral Perception? - Preston J. Werner (Philosophies, 2023)
According to contentful moral perception (CMP), moral properties can be perceived in the same sense as tables, tigers, and tomatoes. Recently, Heather Logue (2012) has distinguished between two potential ways of perceiving a property. A Kantian Property (KP) in perception is one in which a perceiver’s access involves a detection of the property via a representational vehicle. A Berkeleyan Property (BP) in perception is one in which a perceiver’s access to the property involves that property as partly constitutive of the experience itself. In this paper, I set aside generalized arguments in favor of one view or another, and instead ask whether proponents of CMP have reasons to understand moral perception as Kantian or Berkeleyan. I explore three possible explanatory differences—(a) explaining the intrinsic motivating force of moral perceptions, (b) providing a metasemantics for moral properties, and (c) providing an epistemology of the normative authority of moral properties.